Antifungal Activities of Posaconazole and Granulocyte-Macrophage Colony-Stimulating Factor Ex Vivo and in Mice with Disseminated Infection Due to Scedosporium prolificans - Simitsopoulou, M. (American Society for Microbiology, 2004)
Invasive infection due to Scedosporium prolificans is characterized by drug resistance and a high rate of mortality. The effects of posaconazole (POS), an investigational antifungal triazole, murine granulocyte-macrophage colony-stimulating factor (GM-CSF), and their combination against S. prolificans were evaluated ex vivo and in a newly developed murine model of disseminated infection due to this organism. When POS was combined with polymorphonuclear leukocytes from untreated or GM-CSF-treated mice (P < 0.01) ex vivo, it had increased activity in terms of the percentage of hyphal damage. Immunocompetent BALB/c mice were infected with 4 × 10(4) conidia of S. prolificans via the lateral tail vein. At 24 h postinfection the mice were treated with GM-CSF (5 μg/kg of body weight/day subcutaneously), POS (50 mg/kg/day by gavage), both agents, or saline only. Half of the brain, lung, liver, and kidney from each animal were cultured; and the other half of each organ was processed for histopathology. The mean survival times were 7.0 ± 0.3 days for the controls, 7.4 ± 0.4 days for POS-treated mice, 8.0 ± 0.3 days for GM-CSF-treated mice (P = 0.08 compared with the results for the controls), and 7.3 ± 0.3 days for POS-GM-CSF-treated mice. Fungal burdens (determined as the numbers of CFU per gram of tissue) were found in descending orders of magnitude in the kidneys, brains, livers, and lungs. The burdens were significantly reduced in the brains of GM-CSF-treated mice (P < 0.05) and the livers of POS-treated mice (P < 0.05). The numbers of lesions in the organs closely corresponded to the fungal burdens. GM-CSF tended to prolong survival (P = 0.08 compared with the results for the controls). While the combination of POS and GM-CSF showed enhanced activity ex vivo, it did not increase the activities of the two agents against this highly refractory filamentous fungus in mice.